The rhythms of citizens’ leisure and recreation: a case study based on social media data - Zhang, Yuansuo; Wang, Xuejiao; Zhi, Guoqing; Zhou, Huimin; Cui, Na (Frontiers in Ecology and Evolution, 2025)
IntroductionLeisure and recreation behavior has become one of the important lifestyles for urban residents, according to the continuous development of China’s social economy and the improvement of urban residents’ living standards and the spatio-temporal rhythm of these activities presents significant potential for exploration.MethodsThis study investigates the temporal and spatial patterns of citizens’ leisure and recreation activities in Beijing with the social media data from Sina Weibo. Through machine learning and spatial statistical methods, the research analyzes residents’ leisure and recreation behaviors, identifying four main topics: “Popular Nowadays,” “Special Events,” “Scenic Spots,” and “Daily Leisure.”ResultsThe analysis reveals the leisure and recreation activity timing correlates closely with daily work and rest habits, which shows significant differences between weekdays and weekends. The “Popular Nowadays” accounts for 21.9% of leisure and recreation activities, while the “Daily Leisure” represents the largest proportion at 29.1% and shows a marked increase on weekends. Spatially, leisure and recreation activities display a centripetal distribution, with the high activity levels of the city center and main roads, and different leisure and recreation topics have distinct hotpots, including commercial areas, scenic spots, and cultural sites. Notably, the “Special Events” demonstrates a significant increase in activity distance on Saturdays, with an average distance considerably higher than other topics.DiscussionThe study concludes that the dynamic level of leisure and recreation activities is influenced by urban facility distribution and quality, which offer valuable insights for urban planning and “leisure and recreation “space improvement in Beijing.